Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Mozaik - Ranti Ranti; Nurmalina Nurmalina; Melvi Lesmana (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research was motivated by the low fine motor skills of children in group B of Al-Anshor Kindergarten, Pangkalan Tampoi Village, Kerumutan District, Pelalawan Regency. The solution to this problem is the application of the Mosaic method. This research aims to find out whether the Mosaic method can improve fine motor skills in children at Al-Anshor Kindergarten. To improve the fine motor skills of children in group B of the Al-Anshor Kindergarten in Pangkalan Tampoi Village, the Mosaic method will be applied. The subjects in this research consisted of 15 children, 9 girls and 6 boys. The method used in this research was Classroom Action Research (PTK). This classroom action research was carried out in 2 cycles, in each cycle there were 2 meetings, each meeting consisted of the following activities: Planning, Acting, Observation and Reflection. The data collection technique was carried out using observation and documentation. The results of the study showed that there was an increase in children's fine motor skills in each child's indicators starting from Pre-action with an average value of 27% in cycle I, the child's BB value for 1 child was 6.66%. cycle II to 0 children 0%, cycle I MB value 3 children 20%, cycle II to 0 children 0%, cycle I BSH value 7 children 46%, cycle II to 1 child 6.66%, cycle I BSB value 4 children 26.66%, cycle II to 14 children 93.33%. With the increase in children's fine motor skills reaching 90% in the very well developed category, it can be said that the Mosaic method can improve the fine motor skills of children in group B of Al-An Shor Kindergarten, Pangkalan Tampoi Village. Keywords: Fine Motor Skills, Mosaic Method, Classroom Action Research